Effects of tobacco smoke on the expression of virulence genes in Escherichia coli - Shiratsuchi, Akiko; Kidoura, Yuto; Toriba, Akira; Nakanishi, Yoshinobu; Nainu, Firzan (Narra J, 2024)
It is widely acknowledged that smoking exacerbates the severity of infectious diseases. A presumed mechanism involves the damage inflicted by tobacco smoke on the organs of host organisms. In this study, an alternative hypothesis was explored: smoking enhances the virulence of bacteria. This possibility was investigated using Escherichia coli as the bacterial agent and Drosophila as the host organism. Our inquiry focused on the potential gene expression changes in E. coli subsequent to exposure to tobacco smoke. Analysis of the transcription promoter activity of genes encoding proteins within the E. coli two-component system, a regulatory machinery governing gene expression, revealed the activation of twelve out of 50 promoters in response to tobacco smoke. Subsequently, Drosophila was infected with E. coli exposed to tobacco smoke or left untreated. Interestingly, there were no significant differences observed in the survival periods of Drosophila following infection with E. coli, whether treated or untreated with tobacco smoke. Contrary to the initial hypothesis, the findings suggest that while tobacco smoke alters gene expression in E. coli, these changes do not appear to impact bacterial virulence. Although this study has illuminated the influence of tobacco smoke on the gene expression of E. coli, further analyses are necessary to elucidate the implications of these changes. Nevertheless, the results imply that smoking affects not only host organisms but may also exert influence on invading bacteria.